Intrinsically disordered proteins in synaptic vesicle trafficking and release - Snead, David (J Biol Chem, 2019)
The past few years have resulted in an increased awareness and recognition of the prevalence and roles of intrinsically disordered proteins and protein regions (IDPs and IDRs, respectively) in synaptic vesicle trafficking and exocytosis and in overall synaptic organization. IDPs and IDRs constitute a class of proteins and protein regions that lack stable tertiary structure, but nevertheless retain biological function. Their significance in processes such as cell signaling is now well accepted, but their pervasiveness and importance in other areas of biology are not as widely appreciated. Here, we review the prevalence and functional roles of IDPs and IDRs associated with the release and recycling of synaptic vesicles at nerve terminals, as well as with the architecture of these terminals. We hope to promote awareness, especially among neuroscientists, of the importance of this class of proteins in these critical pathways and structures. The examples discussed illustrate some of the ways in which the structural flexibility conferred by intrinsic protein disorder can be functionally advantageous in the context of cellular trafficking and synaptic function.